Pengaruh Kompetensi Keahlian dan Pengurusan Dokumen terhadap Proses Rekruitmen dalam Penempatan Awak Kapal di PT. Bharat Maritim Indonesia - Aurelia Putri Kori Azzahro; Atria Maharani; M. Aji Luhur Pambudi; Sulida Erliyana (Politeknik bumi Akpelni, 2026)
This research is based on the lack of optimal integration between expertise competencies and document management of prospective crew members which has an impact on the effectiveness of the recruitment process in the placement of crew members at PT. Bharat Maritim Indonesia. This study aims to analyze the influence of expertise competencies and document management on the recruitment process in crew placement. The method used is a quantitative descriptive approach using a sample withdrawal using a saturated sample of 40 employees of PT. Bharat Maritime Indonesia which is involved in the recruitment process of the crew. The results of the study showed that competence in expertise and document management had a positive and significant influence on the recruitment process, where the F test showed a Fcal value of 48.833 greater than Ftable 3.25 with a significance level of 0.000 and an R value of 0.852. As much as 72.5% of the recruitment process is influenced by these two variables, while the remaining 27.5% is influenced by other factors such as work experience, education level, and company policies. Thus, improving expertise competencies supported by good document management is an important factor in improving the quality and efficiency of the recruitment process and crew placement.